Respiratory diseases in preschool children in the city of Niš exposed to suspended particulates and carbon monoxide from ambient air - Djordjević, Amelija; Ristić, Goran; Živković, Nenad; Todorović, Branimir; Hristov, Sladjan; Milosević, Lidija (Vojnosanitetski pregled, 2017)
Background/Aim. Analysis of air quality in Serbia indicates that the city of Niš belongs to a group of cities characterized by the third category of air quality (excessive air pollution). The aim of the study was to analyze the degree of causality between ambient air quality affected by particulate matter of 10 µm (PM10) and carbon monoxide (CO) and the incidence of respiratory diseases in preschool children in the city of Niš. Methods. We quantified the influence of higher PM10 concentrations and carbon monoxide comprising motor vehicle exhausts in the city of Niš on the occurrence of unwanted health effects in preschool children by means of the hazard quotient (HQ), individual health risk (Ri), and the probability of cancer (ICR). The methodology used was according to the US Environmental Protection Agency (EPA), and it included basic scientific statistical methods, compilation methods, and the relevant mathematical methods for assessing air pollution health risk, based on the use of attribute equations. Results. Measurement of ambient air pollutant concentrations in the analyzed territory for the entire monitoring duration revealed that PM10 concentrations were significantly above the allowed limits during 80% of the days. The maximum measured PM10 concentration was 191.6 µg/m3, and carbon monoxide 5.415 mg/m3. The incidence of respiratory diseases in the experimental group, with a prominent impact of polluted air was 57.17%, whereas the incidence in the control group was considerably lower, 41.10 %. There were also significant differences in the distribution of certain respiratory diseases. Conclusion. In order to perform good causal analysis of air quality and health risk, it is very important to establish and develop a system for long-term monitoring, control, assessment, and prediction of air pollution. We identified the suspended PM10 and CO as ambient air pollutants causing negative health effects in the exposed preschool children population.